Curcumin targets multiple enzymes involved in the ROS metabolic pathway to suppress tumor cell growth - Yonika Arum Larasati (Nature Portfolio, 2018)
Abstract Curcumin has been reported to exhibit anti-tumorigenic activity; however, since its precise actions remain unclear, its effects are considered to be deceptive. In the present study, we confirmed the anti-tumorigenic effects of curcumin on CML-derived leukemic cells in a xenograft model and in vitro culture system. In vitro pull-down and mass analyses revealed a series of enzymes (carbonyl reductase, glutathione-S-transferase, glyoxalase, etc.) that function in a reactive oxygen species (ROS) metabolic pathway as curcumin-binding targets, the expression of which was up-regulated in human leukemia. Curcumin increased ROS levels over the threshold in leukemic cells, and the antioxidant, glutathione (GSH) and overexpression of curcumin-binding enzymes partially mitigated the up-regulation of ROS and growth inhibition caused by curcumin. These results show that curcumin specifically inhibits tumor growth by increasing ROS levels over the threshold through the miscellaneous inhibition of ROS metabolic enzymes. Curcumin has potential in therapy to regulate ROS levels in tumor cells, thereby controlling tumor growth.